INNOVATIVE TECHNOLOGY-BASED LEARNING MODELS (BLENDED LEARNING, FLIPPED CLASSROOM, AND PROJECT-BASED LEARNING) FOR DEVELOPING CRITICAL, CREATIVE, AND COLLABORATIVE SKILLS: A LITERATURE REVIEW - Kadeni Kadeni; Mohammad Ahmad Bani Amer; Mowafg Masuwd (Adisam Publisher, 2025)
This study aims to examine the effectiveness of innovative technology-based learning models, including blended learning, flipped classrooms, and project-based learning, in developing critical, creative, and collaborative skills. Through a literature review method, this study analyses various studies discussing the implementation and role of technology in supporting adaptive and participatory learning. The results of the study indicate that the integration of technology in these learning models can significantly increase student engagement, facilitate active learning, and strengthen the development of higher-order thinking skills and cooperation among students. These findings emphasise the importance of the planned and systematic use of technology in education as an effort to equip students with essential 21st-century competencies.